EFEKTIVITAS PENERAPAN PEMBELAJARAN IPA FISIKA BERBASIS INKUIRI TERBIMBING TERHADAP PENALARAN FORMAL SISWA DI MTsN NAUMBAI KAMPAR - Putri, Hariyati; ', M. Rahmad; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to describe the effectiveness and improvement of the students formal reasoning by applying guide inquiri learning model at MTsN Naumbai Kampar. Type of this research is a quasi-experimental, with Intact Group Comparisson design. The subject is students class VIII A as experimental class and class VIII B as control class. The data in this research is a score posttest of formal reasoning learning outcome and analysis with descriptive and inferensial analysis. The analysis of data showed absortion of student in the experiment class is higher than the control class on each indicator of formal reasoning. The absorption and learning effectiveness in class experiment is 77,50 with good and effective categori. Result of inferensial analysis using two independent sample t-test, the significant is 0,000, because p < 0.05, then the hypothesis rejected, so there are significant differences between the formal reasoning of students in the experimental class by applying guided inquiry learning model with the control class that implements conventional learning at class VIII MTsN Naumbai Kampar with a level of trust 95 % .With thus be concluded that the application of guided inquiry learning model effectively and can increasing the formal reasoning of students at class VIII MTsNNaumbai Kampar.Key words: Guided Inquiry, Formal Reasoning, Efectiveness